2014
DOI: 10.15430/jcp.2014.19.4.265
|View full text |Cite
|
Sign up to set email alerts
|

Pycnogenol Induces Nuclear Translocation of Apoptosis-inducing Factor and Caspase-independent Apoptosis in MC-3 Human Mucoepidermoid Carcinoma Cell Line

Abstract: Background:Pycnogenol is extracted from the pine bark of a tree known as Pinus pinaster that has variety biological effects. However, its anticancer activity has not yet been completely studied. The aim of this study is to investigate anticancer effect of pycnogenol in MC-3 human mucoepidermoid carcinoma (MEC) cell line.Methods:We describe the effect of anti-cancer of pycnogenol in MC-3 human oral MEC cells using trypan blue exclusion assay, 3-(4,5-dimethylthiazol-2-yl)-(3-carboxymethoxyphenyl)-2-(4-sulphophen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
0
11
1
Order By: Relevance
“…The possible mechanism underlying the cytotoxic effect of PYC has been associated with apoptosis. 16,17 In the study investigating the apoptotic effects of PYC, PYC induced apoptosis in human fibrosarcoma cells (HT1080), using flow cytometric analysis and RNA microarray. 16 In another study, it was reported that PYC significantly decreased cell viability and also induced caspase-independent apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possible mechanism underlying the cytotoxic effect of PYC has been associated with apoptosis. 16,17 In the study investigating the apoptotic effects of PYC, PYC induced apoptosis in human fibrosarcoma cells (HT1080), using flow cytometric analysis and RNA microarray. 16 In another study, it was reported that PYC significantly decreased cell viability and also induced caspase-independent apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PYC induced the translocation of apoptosis-inducing factor into the nucleus and regulated apoptosis. 17 In a study investigating the antitumor effect of PYC, the IC 50 values of PYC in human leukemia cells (HL-60, U937, and K562) were reported to be 150 µg/mL (~516.8 µM), 40 µg/ mL (~137.8 µM), and 100 µg/mL (~344.5 µM), respectively, for 24 h incubation, by propidium iodide exclusion. 18 In another study, in which the apoptotic effect of PYC in human oral squamous carcinoma (HSC-3) cells was investigated by the MTS assay, the IC 50 value of PYC was reported as 20 µg/mL (~68.9 µM) for 24 h incubation.…”
Section: Discussionmentioning
confidence: 99%
“…However, adverse effects of Pyc were observed in an in vitro model of lens cataract formation, accompanied by elevation of [Ca 2+ ] i and mitochondrial death in the cells of lens fibers (Trevithick et al ., ). Diverse apoptotic mechanisms have been suggested for Pyc also in a number of cancer cell lines (Huang et al ., ; Park and Kim, ; Yang et al ., , ). The pathway of mitochondria‐dependent apoptotic cell death has been considered to be both caspase‐dependent (Huang et al ., ; Park and Kim, ; Yang et al ., ) and caspase‐independent (Yang et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Diverse apoptotic mechanisms have been suggested for Pyc also in a number of cancer cell lines (Huang et al ., ; Park and Kim, ; Yang et al ., , ). The pathway of mitochondria‐dependent apoptotic cell death has been considered to be both caspase‐dependent (Huang et al ., ; Park and Kim, ; Yang et al ., ) and caspase‐independent (Yang et al ., ). In addition, reactive oxygen species generation (Park and Kim, ; Yang et al ., ), increase of Bak protein expression (Yang et al ., ), and translocation of apoptosis‐inducing factor into nucleus (Yang et al ., ) may play a role in apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation